Assessment of vulnerability of the groundwater quality at the waste disposal site by using drastic method - Nik Zulhafiz Bin Nek Zulkipli (School of Environmental Engineering, University Malaysia Perlis, 2016)
Increasing population and tremendous urbanisation growth and other factors influence directly the municipal solid waste (MSW) generation in Malaysia. Landfilling is the most frequent waste disposal method worldwide. Year after year, the recognition of landfill leachate impact on environment have forced authorities to fix more and more stringent requirements for pollution control. The evaluation of existing and new landfills requires considerable consideration of environmental factors for the protection of groundwater resources. An important problem associated to landfills is the production of leachates. Leachate that are absorb into the soil can be possibly harming the groundwater system Scientists are deeply concerned with the state of vulnerability of groundwater reservoirs. The initial evaluation of sites can be time-consuming and expensive depending on the assessment approach selected. General planning methods, such as the DRASTIC procedure (Depth water, Recharge rate, Aquifer media, Soil media, Topography, Impact of vadose zone, Conductivity), coupled with the use of analytical or numerical groundwater models can provide useful site selection tools by improving the quality and quantity of analysis. Evaluation of groundwater vulnerability would be performed by using computer programs which are based on Geographical Information System (GIS) in order to facilitate data management and spatial analysis. The study area is between the boundary of Perak and Selangor in Peninsular Malaysia. Most of the places are range low vulnerability to the medium vulnerability. By using the DRASTIC method the vulnerability class of groundwater quality can be determined and the chooses of waste disposal site can effective and also can prevent the contamination to the groundwater system.